Метод тривимірного сканування для задач навігації наземних роботів - Попов, О. О. (ХНУРЕ, 2020)
Tasks of localization and construction of the map of the terrain. The main way to solve this problem is to use SLAM (Simultaneous Localization and Mapping) algorithms. At the moment there are many different SLAM algorithms, differing both in the type of input information, the presentation of the surrounding space in the form of a map, and the methods of processing this information. In this paper, the classification of localization algorithms by the size of the mapped space will be considered.
Keywords: сканування; 3D